Impact of radiation, systemic therapy and treatment sequencing on survival of patients with melanoma brain metastases - Rauschenberg, Ricarda; Bruns, Johannes; Bruetting, Julia; Daubner, Dirk; Lohaus, Fabian; Zimmer, Lisa; Forschner, Andrea; Zips, Daniel; Hassel, Jessica C.; Berking, Carola; Kaehler, Katharina C.; Utikal, Jochen; et al. (European Journal of Cancer, 2019)
Background: Combining stereotactic radiosurgery (SRS) and active systemic therapies (STs) achieved favourable survival outcomes in patients with melanoma brain metastases (MBMs) in retrospective analyses. However, several aspects of this treatment strategy remain poorly understood. We report on the overall survival (OS) of patients with MBM treated with a combination of radiotherapy (RT) and ST as well as the impact of the v-Raf murine sarcoma viral oncogene homolog B (BRAF)-V600 mutation (BRAFmut) status, types of RT and ST and their sequence. Patients and methods: Data of 208 patients treated with SRS or whole brain radiation therapy (WBRT) and either immunotherapy (IT) or targeted therapy (TT) within a 6-week interval to RT were analysed retrospectively. OS was calculated from RT to death or last follow-up. Univariate and multivariate Cox proportional hazard analyses were performed to determine prognostic features associated with OS. Results: The median follow-up was 7.3 months. 139 patients received IT, 67 received TT and 2 received IT and TT within 6 weeks to RT (WBRT 45%; SRS 55%). One-year Kaplan-Meier OS rates were 69%, 65%, 33% and 18% (P <.001) for SRS with IT, SRS with TT, WBRT with IT and WBRT with TT, respectively. Patients with a BRAFmut receiving IT combined with RT experienced higher OS rates (88%, 65%, 50% and 18%). TT following RT or started before and continued thereafter was associated with improved median OS compared with TT solely before RT (12.2 [95% confidence interval CI 9.3–15.1]; 9.8 [95% CI 6.9–12.6] versus 5.1 [95% CI 2.7–7.5]; P =.03). Conclusion: SRS and IT achieved the highest OS rates. A BRAFmut appears to be a favourable prognostic factor for OS. For the combination of RT and TT, the sequence appears to be crucial. Combinations of WBRT and ST achieved unprecedentedly high OS rates and warrant further studies.
CRIS-Team Scopus Importer:2023-03-23
Keywords: BRAF inhibitors; Brain metastases; Immune checkpoint inhibitors; Immunotherapies; Melanoma; Stereotactic radiosurgery; Targeted therapy; Whole brain radiation therapy